Different strokes: Winning strategies in women's (and men's) big bash cricket - Vincent Hogan; Patrick Massey (University College Dublin, UCD School of Economics, 2023)
We analyse winning strategies in the Australian Women's Big Bash Cricket League (WBBL). Our objective is two- fold. First such analysis has potential implications for fan interest, team selection and recruitment. While several studies have analysed winning strategies in men's cricket we are unaware of any such studies for women's cricket. Second, comparing winning strategies in the WBBL and the men's Big Bash League (MBBL) enables us to test the hypothesis that women perform less well than men under pressure. The two competitions are (almost) identical in all aspects other than gender. We find no evidence that play in the women's game is objectively less exciting than then men's game. In fact, we find some evidence that more attacking play is more likely to win in the woman's competition than in the men's.
Keywords: Z23; D24; 330; Sports; Productivity